Active tuberculosis disease among people living with HIV on ART whocompleted tuberculosis preventive therapy at three public hospitals in Uganda - Turinawe, Gaston; Asaasira, Derrick; Kajumba, Margret Banana; Mugumya, Ivan; Walusimbi, Dennis; Tebagalika, Florence Zawedde; Wasswa, Francis Kakooza; Turyasiima, Munanura; Kayizzi, Susan Wendy Wandera; Odwee, Ambrose; Namajja, Khawa; Nakawooya, Mabel; et al. (PloS one, 2024)
Tuberculosis (TB) preventive therapy (TPT) reduces the incidence of TB among people living with the human immunodeficiency virus (PLHIV). However, despite an increase in TPT uptake, TB/HIV coinfection remains stagnant in Uganda especially in areas of increasing HIV incidence such as the Bunyoro sub-region. This study was a retrospective review records (antiretroviral therapy [ART] files) of PLHIV who were active on ART and completed TPTin2019/2020 at three major hospitals in the Bunyoro sub-region, Uganda: Masindi General Hospital, Hoima Regional Referral Hospital, and Kiryandongo General Hospital. The sample size (987) for each facility was determined using a proportionate sampling method to ensure the study’s power and precision. Factors independently associated with acquiring TB disease post TPT were determined using modified Poisson regression analysis. An adjusted prevalence risk ratio (aPRR) with corresponding 95% confidence intervals were reported. The participants’ mean age was 38.23 (±11.70) and the majority were female (64.94%). Overall, 9.63% developed active TB disease post TPT completion. In the adjusted analysis, factors associated with active TB disease were a history of an unsuppressed viral load after TPT (aPRR 4.64 (2.85–7.56), p<0.001), opportunistic infections after TPT completion (aPRR 4.31 (aPRR 2.58–7.2), p<0.001), a history of TB active TB dis ease (aPRR1.60(1.06–2.41), p = 0.026), and chronic illness during or after TPT (aPRR 1.68 (1.03–2.73), p = 0.038). To reduce the development of TB disease post TPT thereby improving the effectiveness of TPT, ART adherence should be emphasized to resolve viral suppression and active management of chronic and opportunistic infections. Further clinical management consideration and research is needed for PLHIV who receive TPT but have a previous history of TB disease.
Keywords: Tuberculosis (TB); Preventive therapy; HIV; Uganda